The Influence of Sales Strategy, Business Concept and Success Indicators on Entrepreneurship with Marketing Management as a Mediating Variable - Nunung Ayu Sofiati; Suhendra, Agus; Sani, Indra; Zaini, Mohamad (Siber International Journal of Digital Business (SIJDB), 2024)
The article on the influence of sales strategy, business concept and success indicators on entrepreneurship with marketing management as a mediating variable is a scientific literature article in the scope of marketing management science. The purpose of this study is to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of marketing management. The research method used is descriptive qualitative. The data collection technique uses literature studies. Data were obtained from previous research that is relevant to this study and sourced from academic online media such as Publish or Perish, Google Scholar, digital reference books and Sinta journals. The results of this article are: 1) Sales Strategy influences Marketing Management; 2) Business Concept influences Marketing Management; 3) Success Indicators influence Marketing Management; 4) Sales Strategy influences Entrepreneurship; 5) Business Concept influences Entrepreneurship; 6) Success Indicators influence Entrepreneurship; and 7) Marketing Management influences Entrepreneurship.